Major Ethical Issues in Marketing “A Descriptive Approach” - Bensalah , Abderrezak (Finance and Business Economies Review, 2021)
A significant number of studies have been conducted in order to show the importance of ethical conducts in the marketing practice, caused by irresponsible practices. The purpose of this paper is to provide a set of marketing ethical issues governing marketing practices, through a conceptual perspective, the proposed framework is based on the presentation of the marketing ethics definition, its role in improving marketing outcomes, and finally, a list of the major ethical issues have been highlighted.